PENGARUH LOAN TO DEPOSIT RATIO (LDR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSETS (ROA) PADA PT BPD JAWA BARAT DAN BANTEN TBK PERIODE 2014 - 2023 - Irman; Nurwita (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the effect of Loan to Deposit Ratio and Debt to Equity Ratio on Return on Assets (ROA) at PT. West Java Regional Development Bank and Banten Tbk. The method used is a quantitative method with an associative approach. The samples used in this research are data contained in reports, credit, third party funds, profit and loss balance sheets, and. other financial ratios as well as existing statistical data and other documents related and required at PT Bank Pembangunan Daerah West Java and Banten (Persero) Tbk. period 2014-2023. The results of this research show that the Loan to Deposit Ratio (LDR) variable partially has a significant influence on Return on Assets (ROA), which is indicated by the t value of 4.316 which is greater than the t table of 2.048, as well as the significance value of 0.003 which is smaller than 0.050 . On the other hand, the Debt to Equity Ratio (DER) variable partially has no significant effect on ROA, with a t value of 1.165 which is smaller than the t table of 2.306, and a significance value of 0.282 which is greater than 0.05. However, simultaneously, LDR and DER have a significant effect on ROA, as evidenced by the fcount value of 12.428 which is greater than the ftable of 4.737, as well as the significance value of 0.005 which is smaller than 0.05.